In situ synchrotron X-ray study of bainite transformation kinetics in a low-carbon Si-containing steel. Issue 17 (22nd November 2017) - Guo, L.; Bhadeshia, H. K. D. H.; Roelofs, H.; Lembke, M. I.
ABSTRACT: The bainite transformation in a low-carbon Si-containing steel has been studied in situ by synchrotron X-rays. While the austenite is homogeneous prior to transformation, the carbon distribution becomes nonuniform as bainite plates form. This is because of the different degrees of physical isolation of films and blocks of residual austenite. The method for converting dilatational strain into bainite volume fraction, using lattice strain as a reference, during isothermal transformation was found to overestimate it. The bainitic and martensitic ferrite did not exhibit a tetragonal unit cell due to the low-carbon content of the steel and the high transformation temperature.